Structural Style Analysis of Maqlob Anticline Using Seismic Data - Ahmed Abbas Hasan; Shahad Adil Al-Qaraghuli; Linaz Anis Fadhil; Muaid Jassim Rasheed; Cristina Dallos Mosquera (Zien Journals, 2023)
The interpretation of the two-dimensional seismic line of the Maqlob anticline to ascertain the structural Style is the main problem in this paper. The geological interpretation and the seismic interpretation were completed simultaneously. One 2D seismic line and the depth contour maps of the three different reflector formations in this region (Top Kurra Chine, Top Najmah, and Top Shiranish) were analyzed. These depth structural maps show that five thrust faults are present in the region. As seen in the interpreted seismic section and depth contour maps, the faults have also been identified as thrust faults and back thrust that created pop-up structures. According to the interpretation of the seismic data, the Maqlob structure is made up of pop-up anticlines and triangular zones as a result of compressional regimes. The triangular zone is seen in the top Najmah Formation reflector
Keywords: Structural Style; Thrust Systems; Pop-up and Triangular Zones; Maqlob Anticline, Iraq